Usage of Virtual Reality Technology in Physiotherapy in Germany: Results from a Survey - Alexander Elser; Maybritt Ohse; Camilla Frankenstein; Madlin Leeuw; Sophie Schiebler; Sandra Schmieder; Syl Slatman; Axel Georg Meender Schäfer (Bioengineering)
With an aging population and an increasing prevalence of non-communicable diseases, Germany’s healthcare system is facing significant challenges that require innovative solutions such as digitalization. Among digital technologies, virtual reality (VR) has shown promise in various healthcare settings; however, its use in physiotherapy practice is unknown. This study aimed to assess the frequency and use of therapeutic VR among physiotherapists in Germany and to identify barriers to its adoption. A cross-sectional survey of 296 physiotherapists was conducted, with responses indicating that only 2.7% had used therapeutic VR in the past year. Most physiotherapists were unfamiliar with VR therapy, suggesting that lack of awareness is the primary barrier. Despite limited current use, a significant proportion of physiotherapists were open to integrating VR technologies in the future. Our findings highlight the need for increased information about therapeutic VR within the physiotherapy community and suggest potential growth as awareness and institutional support increases. Future strategies should focus on promoting the benefits of VR and integrating it into reimbursement frameworks to facilitate wider adoption in patient care.